Analisis Efektivitas Biaya Penggunaan Antihipertensi Kombinasi Dua Obat Pada Pasien Hipertensi Rawat Jalan Di Rumah Sakit Umum Daerah Dr. Moewardi Tahun 2012 - Ernawati, Yuli; , Dr. dr. EM. Sutrisna, M.Kes; , Tanti Azizah Sujono, M.Sc., Apt (2016)
Hypertension is one of the major factors of risk of death from cardiovascular disorders that result in 20-50% of all deaths. Health financing in Indonesia increase, the cost-effectiveness analysis is needed in order to assist in decision making these medicines are effective benefits and cost. This study aims to determine the antihypertensive combination of the most cost-effective in the Hospital Dr. Moewardi in 2012. This study is a non-experimental descriptive. The data collection was done retrospectively based on medical records, laboratory and administrative price ceilings on drugs. Cost-effectiveness analysis was done by comparing large direct medical costs on average per month against the percentage of patients reaching blood pressure targets based on parameter ACER. The results showed 8 pattern combinations used patient is beta blockers with ACE-inhibitor, ARBs with hidrochlorothiazid, ARB with CCB, ARB with beta blockers, ACE-inhibitor with diuretics hidrochlorothiazid, ACE-inhibitors with furosemide, ACE-inhibitorwith ARBs, ACE -Inhibitor with CCB. The pattern of treatment which is the most cost-effective for patients with hypertension based on effectiveness of decreasing blood pressure to reach the target was with ACE-inhibitors with hidrochlorothiazid with amounted490,69 ACER and ICER -13.663,68.